2013
DOI: 10.4321/s0213-61632013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive compulsive phenomenology in a sample of Egyptian adolescent population

Abstract: Background and Objectives: Obsessive symptoms among children and adolescent age groups are increasing, an observation made by mental health professionals working with this age group. Our epidemiological study targeted secondary school students to estimate the prevalence of obsessive symptoms, obsessive compulsive disorder and their different obsessive compulsive contents. Methods: The study is cross sectional carried on 1299 secondary school students, the sample size was chosen based on an estimated Obsessive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For instance, a study conducted in Cairo found an incidence of OCD of 2.5% among 1,000 undergraduates attending a university clinic [ 40 ]. Another study revealed that the prevalence of Obsessive-Compulsive Symptoms (OCS) is 38.7% in secondary schools [ 41 ]. In a study conducted by Taher et al (2021) in Iraq, it was reported that a significant number, 1153 (70.1%), reported experiencing mental symptoms, with worry and stress being the most common, affecting 674 (25.9%) and 617 (23.7%) of the students respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study conducted in Cairo found an incidence of OCD of 2.5% among 1,000 undergraduates attending a university clinic [ 40 ]. Another study revealed that the prevalence of Obsessive-Compulsive Symptoms (OCS) is 38.7% in secondary schools [ 41 ]. In a study conducted by Taher et al (2021) in Iraq, it was reported that a significant number, 1153 (70.1%), reported experiencing mental symptoms, with worry and stress being the most common, affecting 674 (25.9%) and 617 (23.7%) of the students respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of OCS among Nigerian adolescents was 37.8%. In Egypt, various studies have reported prevalence rates of 13.3%, 18.4% and 43.1% with measures other than the OCI-CV12–14. About a decade ago, a study in Nigeria reported that approximately 40% of Nigerian students may exhibit OCS48.…”
Section: Discussionmentioning
confidence: 99%
“…It ranges from 2.7% to 19.4% in the developed western countries611. The few studies in African countries reported prevalence rates ranging from 13.3% to 43.1%12–14. However, in spite of these various studies, OCS in children and adolescents are still underestimated and understudied2.…”
Section: Introductionmentioning
confidence: 99%